Generalization of Some Coupled Fixed Point Results on Partial Metric Spaces - Wasfi Shatanawi; Hemant Kumar Nashine; Nedal Tahat (International Journal of Mathematics and Mathematical Sciences)
Using the setting of partial metric spaces, we prove some coupled fixed point results. Our results generalize several well-known comparable results of H. Aydi (2011). Also, we introduce an example to support our results.